Acorn bread: A traditional food of the past in Sardinia (Italy) - Claudia, Pinna (Journal of Cultural Heritage, 2013)
Acorn bread, known as Pan’Ispeli in Sardinian, constituted a precious source of nutrition over the ages. Especially widespread in Ogliastra, it was made with somewhat unusual ingredients, including ash and clay, and is considered a unique food by many historians. So much so that the women of the town of Baunei took pride in their skill at making acorn bread and apparently sold it at a higher price than regular wheat flour bread. The laborious process of preparation of acorns for bread-making is said to have been a ceremony with religious connotations, to such an extent that the ingredients came only from plants and areas that were well known by the elders. It was a ritual passed down from generation to generation. Although acorn bread is no longer part of today's diet in Sardinia, it is still remembered by some of the elderly people of our island and is on occasion still made for village festivities.
Keywords: acorns; Bread; Clay; Coeliac disease sufferers; Quercus; Sardinia

The effect of starch isolation method on physical and functional properties of Portuguese nut starches. II. Q. rotundifolia Lam. and Q. suber Lam. acorns starches - Correia, Paula Reis; Nunes, Maria Cristiana; Beirão-da-Costa, Maria Luísa (Food Hydrocolloids, 2013)
A new starch was isolated from fruits of two acorn species, Quercus rotundifolia and Quercus suber by alkaline (A3S) and enzymatic (ENZ) methods and physical and functional properties were studied. The isolation method induced changes in most of those properties in the isolated starches, mainly in resistant starch content, syneresis, pasting, thermal and rheological properties. Isolated acorn starches presented high amylose content (53e59%) and resistant starch content (30.8e41.4%). Acorn starches showed limited and similar solubility values and swelling power values, showing a gradual increase from 60 C to 90 C. The pasting temperatures ranged from 67.5 to 72.0 C and pastes did not present breakdown, which is suggestive of a high paste stability of acorn starches during heating. At ambient temperature the turbidity and syneresis values were low, but when held at freezing temperatures the syneresis signiﬁ- cantly increased. Thermal analysis revealed that the acorn starches easily undergo transition phenomena as shown by the low To and enthalpy values (4.1e4.3 J/g), these effects were more evident in starches isolated by ENZ method. Pastes are more elastic than viscous and form strong gels after cooling. Q. suber starch was shown to be more sensitive to the effect of isolation method. Generally, starch isolated by enzymatic method presented less interesting functional properties, since this isolation procedure greater affected the raw structure of starches
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: acorns; Functional properties; isolation method; rheological properties; starch; thermal properties

Extracts from Quercus sp. acorns exhibit in vitro neuroprotective features through inhibition of cholinesterase and protection of the human dopaminergic cell line SH-SY5Y from hydrogen peroxide-induced cytotoxicity - Custódio, Luísa; Patarra, João; Alberício, Fernando; Neng, Nuno Rosa; Nogueira, José Manuel Florêncio; Romano, Anabela (Industrial Crops and Products, 2013)
In this work non polar (hexane) and polar (methanol and hot water) extracts of cork oak (Quercus suber) and holm oak (Quercus ilex) acorns were evaluated for the first time for in vitro neuroprotective properties, by determining their in vitro inhibitory activity against acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) and their capacity to attenuate hydrogen peroxide-induced injury in the human dopaminergic cell line SH-SY5Y. Total content of phenolics, tannins and flavonoids, HPLC profile of the main phenolic compounds and antioxidant activity were also determined. The methanol extracts showed inhibitory activities against AChE and BChE. The best results toward AChE were obtained with cork oak extract (69.4% inhibition at the concentration of 1 mg/ml), while for BChE the highest inhibition (46% inhibition at the concentration of 1 mg/ml) was obtained with holm oak. Moreover, methanol extracts were able to prevent oxidative stress-induced cytotoxicity in SH-S5SY cells. The methanol extract of holm oak exhibited the highest RSA, with values of 63.8% and 49.7% on DPPH and ABTS radicals at the concentration of 1 mg/ml, respectively. In general the extracts exhibited no reducing potential. The methanol extract from cork oak acorns had the highest content in phenolic compounds (25.2 mg GAE/g, DW), while the water extracts had the maximum level of flavonoids (1.7 mg RE/g, DW). Tannins were present in higher amounts in the water extract of holm oak (91.6 CE/g, DW). The main compounds in the methanol extract from holm oak acorns were (−)-epicatechin and catechol, while gallic acid and (+)-catechin were the main constituents of the methanol extract from cork oak acorns. Our results indicate that cork and holm oak acorns provide a valuable source of biomolecules useful for alleviating symptoms associated with Alzheimer's disease and other neurodegenerative ailments.
Keywords: acorns; Alzheimer's; Cholinesterase; Dementia; Mediterranean trees; Neurological disorders

Masting in oaks: Disentangling the effect of flowering phenology, airborne pollen load and drought - Fernández-Martínez, Marcos; Belmonte, Jordina; MARÍA ESPELTA, JOSEP (Acta Oecologica, 2012)
Quercus species exhibit an extreme inter-annual variability in seed production often synchronized over large geographical areas (masting). Since this reproductive behavior is mostly observed in anemophilous plants, pollination efﬁciency is suggested as one hypothesis to explain it, although resource-based hypotheses are also suggested as alternatives. We analyzed the effect of ﬂowering phenology, airborne pollen presence and meteorological conditions in the pattern of acorn production in mixed evergreendeciduous oak forests (Quercus ilex and Quercus pubescens) in NE Spain for twelve years (1998e2009). In both oaks, higher temperatures advanced the onset of ﬂowering and increased the amount of airborne pollen. Nevertheless, inter-annual differences in pollen production did not inﬂuence acorn crop size. Acorn production was enhanced by a delay in ﬂowering onset in Q. ilex but not in Q. pubescens. This suggests that in perennial oaks a larger number of photosynthates produced before ﬂowering could beneﬁt reproduction while the lack of effects on deciduous oaks could be because these species ﬂush new leaves and ﬂowers at the same time. Notwithstanding this effect, spring water deﬁcit was the most relevant factor in explaining inter-annual variability in acorn production in both species. Considering that future climate scenarios predict progressive warmer and dryer spring seasons in the Mediterranean Basin, this might result in earlier onsets of ﬂowering and higher water deﬁcits that would constrain acorn production.
Keywords: acorns; Drought; Mediterranean; Pollination efﬁciency hypothesis; Quercus spp.; Resource-based hypotheses

Acorn production is linked to secondary growth but not to declining carbohydrate concentrations in current-year shoots of two oak species - Alla, Arben Q.; Camarero, J. Julio; Maestro-Martínez, Melchor; Montserrat-Martí, Gabriel (Trees, 2011)
In trees, reproduction constitutes an important resource investment which may compete with growth for resources. However, detailed analyses on how growth and fruit production interact at the shoot level are scarce. Primary canopy growth depends on the development of current-year shoots and their secondary growth might also inﬂuence the number and size of fruits supported by them. We hypothesise that an enhanced thickening of currentyear shoots is linked positively to acorn production in oaks. We analysed the effect of acorn production on shoot growth of two co-occurring Mediterranean oak species with contrasting leaf habit (Quercus ilex, Quercus faginea). Length and cross-sectional area of current-year shoots, apical bud mass, number of leaves and acorns, xylem and conductive area, number of vessels of acorn-bearing and non-bearing shoots were measured in summer and autumn. Nitrogen and carbohydrates analyses were also performed in stems and leaves of both shoot types. Stem cross-sectional area increased in acorn-bearing shoots when compared with non-bearing shoots for both species and such surplus secondary growth was observed since summer. In bearing shoots, the total transversal area occupied by vessels decreased signiﬁcantly from basal to apical positions along the stem as did the xylem area and the number of vessels. Leaves of bearing shoots showed lower nitrogen concentration than those of non-bearing shoots. Carbohydrate concentrations did not differ in stems and leaves as a function of the presence of acorns. Such results suggest that carbohydrates may preferentially be allocated towards reproductive shoots, possibly through enhanced secondary growth, satisfying all their carbon demands for growth and reproduction. Our ﬁndings indicate that acorn production in the two studied oaks depends on shoot secondary growth.
Keywords: acorns; Mediterranean climate; nitrogen; non-structural carbohydrates; Quercus faginea; quercus ilex subsp. ballota; Stem diameter; Xylem

Amido resistente em diversas fontes não convencionais de amido - Fontinha, C.; Correia, Paula (RE, 2010)
Resistant starch is not degraded in the small intestine, leading to a beneficial health effect like the dietetic fibre has. In this work resistant starch content was determined on flours and starches extracted from two varieties of chestnuts (Castanea sativa Mill), Longal and Martainha, and two acorn species (Quercus rotundifolia, Quercus suber). Flours were produced by milling the fruits after drying at different temperatures, 40º C, 50º C, 60ºC e 70ºC. After, starch was isolated from flours by two different extraction methods: physicochemical and enzymatic. Resistant starch content was higher on the flours obtained from the fruits dried at 60ºC, with values of 46,8%, 36,5%, 39,9% e 43,9%, respectively for Longal and Martainha chestnuts, and acorns Quercus rotundifolia, Quercus suber. The physicochemical method presented higher content of resistant starch for all the materials. It seems that drying fruits at 60ºC and the use of the physicochemical isolation method for starch from flours obtained from fruits dried at this temperature preserved better the starch integrity.
Keywords: acorns; Chestnuts; resistant starch

Effects of herbage ingestion upon ileal digestibility of amino acids in heavy Iberian pigs fed on an acorn-based diet - Garcia-Valverde, R.; Nieto, R.; Aguilera, J. F. (JOURNAL OF ANIMAL PHYSIOLOGY AND ANIMAL NUTRITION, 2010)
P>We conducted two experiments with heavy Iberian pigs to determine the ileal digestibility of amino acids (AA) in acorns and freshly cut herbage, and the effects of adding fresh herbage upon the supply of ileal digestible AA when pigs were fed on holm-oak acorns. In Experiment 1, carried out in cannulated pigs of 107 kg bodyweight (BW), daily intake of acorns reached 44.9 g DM/kg0.75 BW. Arg, His and Thr showed the lowest apparent ileal digestibility (AID) values, whereas Met, the branched-chain AA and Phe had the highest coefficients. The AID of total EAA was 0.716 but only 0.222 for NEAA. Most of the digestive and absorptive processes of acorn protein occurred before the hindgut. Acorn provides (per kg DM) 2.27 g apparent ileal digestible Lys and 22.7 g apparent total digestible AA. Standardized ileal digestibility (SID) values for EAA, NEAA and total AA were 0.924 +/- 0.020, 0.784 +/- 0.041 and 0.860 +/- 0.029. In Experiment 2 fresh herbage was given to six cannulated Iberian pigs of 140 kg either as a single feed (13.7 g DM/kg0.75 BW) or as a supplement to acorns (28.4 g DM/kg0.75 BW). When only freshly cut forage was offered the AID of the EAA, NEAA and total AA was close to 0.65 and supplied (per kg DM ingested) 5.61 g AID Lys and 91.7 g digestible AA. Standardized ileal values were 0.744 +/- 0.023, 0.912 +/- 0.038 and 0.831 +/- 0.030 respectively. The addition of fresh forage to the acorns led to a significant decrease in AID of AA in acorn due to digesta transfer to the hindgut: His (p < 0.01), Met (p < 0.001), Phe (p = 0.092), Thr (p < 0.05) and Val (p < 0.05), but Arg, Lys and the branched-chain AA remained unaffected. The main contribution of herbage to AA nutrition of the grazing Iberian pig relies mainly on increasing the supply of digestible AA for pig tissues.
The following values have no corresponding Zotero field: pub-location: COMMERCE PLACE, 350 MAIN ST, MALDEN 02148, MA USA publisher: WILEY-BLACKWELL PUBLISHING, INC
Keywords: acorns; amino acids; digestibility; herbage; iberian pig

Parsons on Pigs and Acorns* - Gade, Daniel W. (Geographical Review, 2010)
Many articles in the Geographical Review hold stories that resonate in the history of geography only when the passage of time provides the necessary detachment to put these accounts into a context of larger signiﬁcance. The circumstances behind the selection of a particular topic, vicissitudes of the research phase, personality of the author, and exchanges during the editorial process that bring it to publication together provide insight into the diﬀerent layers of geographical scholarship. To all that can be added another dimension: explaining the impact that the piece of writing has had on individuals who have read it. One article in the Geographical Review profoundly aﬀected the formation of my geographical imagination. It did so without appealing to any theory, showcasing some dazzling new technique, harboring an advocacy agenda, or exhorting the reader in any way. Now, nearly half a century after its publication, this text opened another level of reﬂection about its content, author, journal, editor, and changes in the place that was under study.
Keywords: acorns; Dehesa; Iberian ham (voyant); Oak woodland; pigs

Effects of herbage ingestion on the digestion site and nitrogen balance in heavy Iberian pigs fed on an acorn-based diet - Garcia-Valverde, R.; Nieto, R.; Lachica, M.; Aguilera, J. F. (LIVESTOCK SCIENCE, 2007)
We conducted two experiments in heavy-weight Iberian pigs to determine: a) the effect of lysine or protein addition - the former as L-lysine-HCl, the latter by fresh cut herbage supplementation - on protein deposition when they were fed on holm-oak acorns; b) the digestibility of energy and nutrients in acorns and freshly cut, mixed herbage; and c) a possible change in the partition of digestion along the gastro-intestinal tract of the pigs fed on acorns with the inclusion of herbage. In Experiment 1, carried out in eight cannulated pigs, the daily intake of acorns reached 44.9 g DM/kg(0.75) BW and the addition of 0.58 g L-lysine/kg of whole acorns failed to alter N retention significantly (P > 0.05). We obtained high coefficients for the apparent total-tract digestibility of dry matter (ApDM(tt), 0.84) and organic matter (ApOM(tt), 0.86) and of gross energy (ApGE(tt), 0.84) in whole acorns. The corresponding ileal values were 0.71, 0.74 and 0.74. The N balance was on average - 1.08 g/day. In Experiment 2, fresh herbage containing principally legumes was offered to six cannulated Iberian pigs of 140 kg either as a single feed (13.7 g DM/kg(0.75) BW) or as a supplement to acorns (28.4 g DM/kg(0.75) BW; in this case the herbage accounted for 22% of the daily DM intake). The apparent ileal digestibilities of OM and GE for herbage accounted for 70 to 77% of the values observed at total-tract level (0.65 and 0.64 respectively). N retention reached 4.21 g/day. Average ApDM(tt), ApOM(tt) and ApGE(tt) in the herbage/whole-acorn mixture were slightly above 0.74. The intake of freshly cut herbage as complementary feed to acorns resulted in a significant transference of digesta from the small intestine to the hind gut together with a substantial decrease in ileal digestibility of nutrients and energy (P < 0.001) and a moderate decline in digestibility at throughout the whole tract (P < 0.01-P < 0.001). On the other hand, the apparent digestibility of total N increased (P < 0.001) and 31% of the N apparently digested was retained in the body of the pigs. We also observed a substantial decrease in the precaecal digestion of the DM (P < 0.01), OM (P < 0.01) and GE (P < 0.05) in acorn kernels. We concluded that the main contribution of herbage to the overall nutrient supply to the grazing Iberian pig would rely upon the provision of amino acid N and also of available minerals, both present in low quantities in acorns. (C) 2007 Elsevier B.V All rights reserved.
The following values have no corresponding Zotero field: pub-location: PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS publisher: ELSEVIER SCIENCE BV
Keywords: acorns; digestibility; energy value; herbage; iberian pig

Common cranes Grus grus and habitat management in holm oak dehesas of Spain - Aviles, J. M. (BIODIVERSITY AND CONSERVATION, 2004)
Changes in agricultural policies have favored tree clearing and removal of shrubs to favor intensive farming in the holm oak Quercus ilex dehesas of Iberia. The effect of these changes for bird species wintering in this agricultural landscape has been rarely analyzed. Here the effects are studied of farming changes in traditional holm oak dehesas on population size, social structure and time budget of common cranes Grus grus in eight traditional wintering sites in Spain. The role of acorn availability, the principal winter food of the species, in relation to management is also assessed. The number of cranes in each wintering area was not related to degree of agricultural intensification, nor to the availability of acorns. However, crane flock size decreased, and the relative occurrence of isolated family groups increased in less intensively transformed wintering areas characterized by the predominance of fallow lands. The age composition of crane flocks varied with acorn availability since more juveniles were reported in areas with relatively lower acorn availability. Time budget was also related to acorn availability, since cranes spent relatively more time preening in those wintering areas with higher availability of acorns. Globally evidence suggests the need to maintain the fallow land (posios) to sustain the wintering populations of cranes in Iberia, since this agro-grazing system maintains most of the juvenile cranes using the western migratory route.
The following values have no corresponding Zotero field: pub-location: VAN GODEWIJCKSTRAAT 30, 3311 GZ DORDRECHT, NETHERLANDS publisher: KLUWER ACADEMIC PUBL
Keywords: acorns; agricultural policies; holm oak dehesas

Comparison between ethanol and hexane for oil extraction from Quercus suber L. fruits - Ferreira-Dias, Suzana; Valente, Dina G.; Abreu, José M. F. (Grasas y Aceites, 2003)
The aim of this study was to (i) evaluate the feasibility of replacing n -hexane with ethanol for the extraction of oil from Quercus suber fruits and (ii) optimize, at lab scale, sample preparation and extraction time for both solvents used ( n -hexane vs . anhydrous ethanol). For both solvents, the effect of the conditioning process on extraction yield was evaluated. Therefore, a full factorial design was used as a function of four variables: dehulling (with vs . without husks), and thermal treatment of the crushed material (40ºC vs . 75ºC), at different times (5 min vs . 120 min) and pressures (10 kPa vs. 100 kPa). Higher oil yields were obtained with n -hexane when dehulled fruits were conditioned under atmospheric pressure. Better yields were obtained with n -hexane, when dehulled material was treated at 75ºC for 90 min. Ethanol was not adequate for oil extraction from Quercus fruits, since other materials rather than oil were also extracted.
Keywords: acorns; Ethanol; Extraction; Hexane; Oil; Quercus

Vertebrate predation on Holm Oak, Quercus ilex, acorns in a fragmented habitat: effects on seedling recruitment - Santos, T.; Tellería, J. L. (Forest Ecology and Management, 1997)
Rodent and avian consumption of Holm Oak, Quercus ilex, acorns were examined in central Spain during two high-production seasons, 1990-1991 and 1993-1994, in 1 and 3 large stands and in 6 and 10 small stands (0.2-12 ha) respectively, to study the effects of vertebrate predation on seedling recruitment. Previous data indicate that wood mouse abundance is much higher in small stands. Tree size, frequency of acorn-bearing oaks and acorn abundance were similar in the two sizes of forest stands. Overall acorn consumption was 33.7 times higher in the small stands compared to that in the large stands in 1991, and 3.1 times larger in 1994. Consumption of acorns by mice in the small stands was 49 and 95 times greater than that by birds in the first and second year, respectively. Seedling recruitment was significantly higher in the large stands in both study seasons. Regeneration by ramets was roughly similar in small and large stands in both seasons. Thus, predation by mice was apparently responsible for the failure of sexual reproduction in the small stands. The results suggest that vegetative regeneration might be the prevalent reproductive method of Holm Oaks in small forest tracts.
Keywords: acorns; Forest fragmentation; oak; Seedling; Vertebrate predation

Metal contamination in leaves and fruits of holm-oak (Quercus rotundifolia Lam.) trees growing in a pyrites mining area at Aljustrel, Portugal - Fernandes, J. C.; Henriques, F. S. (Water, Air, & Soil Pollution, 1989)
Pyrites extraction at Aljustrel mines, south Portugal, is causing severe metal pollution of soil, water and air, leading to a growing concern with environmental degradation in the mining area and its surroundings. In this work we measured levels of Fe, Mn, Zn, Cu, and Pb in leaves and fruits of holm-oak (Quercus rotundifolia Lain.) trees growing at the outskirts of the mining area. The trees showed pronounced stunting, reduced leaf size and extensive necrotic and chlorotic spotting. The leaves from trees growing in the area under study had much higher concentrations of metals than the controls - ca. 50 times higher for Cu, 20 times for Pb and Zn, 10 times for Fe, and 2 times for Mn - but is is possible that part of the metals associated with the leaves are actually retained in the dense hair cover present on their lower surface. The acorns from the contaminated areas were also metal polluted, particularly with Fe, Zn, and Cu, and this finding raises the threat of animal and human health hazards, since these fruits are commonly used for feeding livestock and are occasionally consumed directly by man. 1.
Keywords: acorns; holm oak (voyant); leaves; Metal pollution